Modern Approach to Miscarriage of Pregnancy - Abdurasulovna, Kamilova Iroda; Shuxratovna, Sharipova Dildora (Researchparks Publishing, 2023)
This review article is devoted to the problem of miscarriage, premature birth, developmental etiopathogenesis and modern approaches to the management and treatment of this pathology.